Well-defined cyclic polymer synthesis via an efficient etherification-based bimolecular ring-closure strategy - Sharma, Sandeep; Ntetsikas, Konstantinos; Ladelta, Viko; Bhaumik, Saibal; Hadjichristidis, Nikos (Polymer chemistry, 2021)
The synthesis of cyclic polymers on a large scale is a challenging task for polymer scientists due to the requirement of ultra-high dilution conditions. In this paper, we demonstrate an alternative method to prepare cyclic polymers with moderate dilution and up to 1 gram scale. We employed a simple Williamson etherification reaction to prepare cyclic polymers with a good solvent/non-solvent combination. In this way, various polystyrene (PS) and polyethylene glycol (PEG) cyclic homopolymers were synthesized. Anionic polymerization using high vacuum techniques combined with the postpolymerization reaction was used to generate linear dihydroxy PS precursors. The synthesized linear and cyclic homopolymers were fully characterized using various spectroscopic and analytical techniques, such as size exclusion chromatography (SEC), matrix-assisted laser desorption/ionization time-of-flight mass spectroscopy (MALDI-TOF-MS), and differential scanning calorimetry (DSC). Detailed nuclear magnetic resonance (NMR) spectroscopic studies were also performed to obtain the complete structural information of the synthesized polymers.